1979
DOI: 10.1159/000460173
|View full text |Cite
|
Sign up to set email alerts
|

Studies with Timed-Pregnant Squirrel Monkeys (Saimiri sciureus)

Abstract: Timed-pregnant monkeys were produced in a large nonhabituated colony of Saimiri sciureus of Bolivian origin. In a colony of 373 females and 40 males, 277 females (74%) were considered to be inseminated, based on microscopic observation of sperm and/or detection of a coagulum (plug) in the vagina. Forty-six full-term progeny were delivered. The mean gestational period was 152.5 days (SD = 3.9 days). For continuous cohabitation, the median time to insemination was five days, with 75% of inseminations occurring w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…The mean gestational length of 147.5 d (21 weeks) in the leadexposed group was slightly lower than the mean length of 152 (SD 3.9) d which has been reported for a large unexposed group of captive Bolivian squirrel monkeys (48). However, comparisons with a series of unexposed squirrel monkey fetuses of known ages (unpublished results) showed that the foot length, body weight, and cerebral weight of the lead-exposed offspring were small at birth for the length of gestation (ie, similar to normal fetuses of about 20 to 21, 20 and 18 to 21 or more weeks of age, respectively).…”
Section: Effects On Pregnancy and The Fetal Braincontrasting
confidence: 66%
See 1 more Smart Citation
“…The mean gestational length of 147.5 d (21 weeks) in the leadexposed group was slightly lower than the mean length of 152 (SD 3.9) d which has been reported for a large unexposed group of captive Bolivian squirrel monkeys (48). However, comparisons with a series of unexposed squirrel monkey fetuses of known ages (unpublished results) showed that the foot length, body weight, and cerebral weight of the lead-exposed offspring were small at birth for the length of gestation (ie, similar to normal fetuses of about 20 to 21, 20 and 18 to 21 or more weeks of age, respectively).…”
Section: Effects On Pregnancy and The Fetal Braincontrasting
confidence: 66%
“…Analy ses of a series of fetal brains from squirrel monkeys (unpublished results) indicated that the cerebral development at nine weeks of gestation is comparable to that at about 12 weeks' gestation in humans, a time at which the second wave of neuroblasts aimed for the human cerebral cortex is still migrating (44). Acco rding to others (48) and our own experience, the risk for spontaneous abortion is much smaller from about this age onward, compared to just a few weeks earlier, and thus the probability of selecting resistant fetuses or placentas is minimized if exposure begins at this age.…”
Section: Exposure To Lead Acetatementioning
confidence: 83%
“…Monitoring female reproduction by cyclical changes in vaginal cytology (e.g. changes in vaginal epithelial cornification), such as is done in rodents, is not commonly used in assessing monkeys but has been evaluated for those nonhuman primates with no or limited menstrual flow, primarily prosimians and New World monkeys (Travis and Holmes, 1974;Hendrickx and Newman, 1978;Stolzenberg et al, 1979;Dukelow, 1983;Nagle and Denari, 1983;Izard and Rasmussen, 1985;Gluckman et al, 2004).…”
Section: Detection Of Ovarian Cycle Phasementioning
confidence: 99%
“…It is known that gestation length in squirrel monkeys is highly variable, with values from studies using reliable methods to assess the date of conception ranging from 137 to 175 d (Goss et al, 1968;Jarosz et al, 1977;Kerber et al, 1977;Stolzenberg et al, 1979). There are some suggestions that gestation length in squirrel monkeys may be more variable than in other primates and that this may be linked to the fact that births are synchronized within squirrel monkey groups (Boinski, 1987;Hartwig, 1996).…”
Section: Discussionmentioning
confidence: 99%